Menakar Perkembangan Perlindungan Hak Asasi Manusia Dalam Prespektif Konstitusi Indonesia - Kurnia, Kamal Fahmi; Hendryan, Dery (VIVA THEMIS, 2025)
Human rights are fundamental rights inherent in every human being without exception that need to be maintained, respected and protected by every human being, society and the state. Law No. 39/1999 on Human Rights is one of the most important legal instruments in the context of the protection and enforcement of human rights in Indonesia. The protection of human rights is one of the main pillars in a modern legal and constitutional structure. The conception of human rights is regulated in the 1945 Constitution of the Republic of Indonesia (UUD 1945) in articles 28A to 28J. The existence of basic rights will create a healthy balance between state power and individual freedom. After independence, the protection of human rights became more advanced with the existence of many protection institutions such as KOMNAS HAM. However, there are still those who try to revive systematic violence and discrimination against minority groups of people